Gold‐Catalyzed Regiospecific Annulation of Unsymmetrically Substituted 1, 5‐Diynes for the Precise Synthesis of Bispentalenes. Issue 52 (28th August 2019) - Tavakkolifard, Sara; Sekine, Kohei; Reichert, Lisa; Ebrahimi, Mina; Museridz, Ketevan; Michel, Elena; Rominger, Frank; Babaahmadi, Rasool; Ariafard, Alireza; Yates, Brian F.; Rudolph, Matthias; Hashmi, A. Stephen K.
Abstract: Precise control of the selectivity in organic synthesis is important to access the desired molecules. We demonstrate a regiospecific annulation of unsymmetrically substituted 1, 2‐di(arylethynyl)benzene derivatives for a geometry‐controlled synthesis of linear bispentalenes, which is one of the promising structures for material science. A gold‐catalyzed annulation of unsymmetrically substituted 1, 2‐di(arylethynyl)benzene could produce two isomeric pentalenes, but both electronic and steric effects on the aromatics at the terminal position of the alkyne prove to be crucial for the selectivity; especially a regiospecific annulation was achieved with sterically blocked substituents; namely, 2, 4, 6‐trimetyl benzene or 2, 4‐dimethyl benzene. This approach enables the geometrically controlled synthesis of linear bispentalenes from 1, 2, 4, 5‐tetraethynylbenzene or 2, 3, 6, 7‐tetraethynylnaphthalene. Moreover, the annulation of a series of tetraynes with a different substitution pattern regioselectively provided the bispentalene scaffolds. A computational study revealed that this is the result of a kinetic control induced by the bulky NHC ligands. Abstract : Give me five : The regiospecific annulation of unsymmetrically substituted 1, 2‐di(arylethynyl)benzene derivatives is reported. Both electronic and steric effects on the aromatic moieties of the substrates are crucial for the selectivity. Moreover, the annulation of a series of differently substituted tetraynes regioselectively provided the corresponding bispentalenes (see scheme). The selectivity of this transformation is rationalized by computational studies, and the opto‐electronic properties of the obtained bispentalene derivatives are also reported.